Self-fulfilling crises in the Eurozone: An empirical test - Paul De Grauwe; Yuemei Ji (Center for Economic Studies and ifo Institute (CESifo), 2012)
We test the hypothesis that the government bond markets in the Eurozone are more fragile and more susceptible to self-fulfilling liquidity crises than in stand-alone countries. We find evidence that a significant part of the surge in the spreads of the PIGS countries in the Eurozone during 2010-11 was disconnected from underlying increases in the debt to GDP ratios and fiscal space variables, and was the result of negative self-fulfilling market sentiments that became very strong since the end of 2010. We argue that this can drive member countries of the Eurozone into bad equilibria. We also find evidence that after years of neglecting high government debt, investors became increasingly worried about this in the Eurozone, and reacted by raising the spreads. No such worries developed in stand-alone countries despite the fact that debt to GDP ratios and fiscal space variables were equally high and increasing in these countries.
Keywords: F00; 330; Eurozone; multiple equilibria; self-fulfilling crises; Öffentliche Anleihe; Rentenmarkt; Marktliquidität; Zinsdifferenz; Risikoprämie; Finanzmarktkrise; Öffentliche Schulden; Gleichgewicht; Eurozone; Welt